A Randomized Study Assessing the Effect of Diet in Cats with Hypertrophic Cardiomyopathy. (3rd April 2014) - Freeman, L.M.; Rush, J.E.; Cunningham, S.M.; Bulmer, B.J.
<x xml:space="preserve">Abstract</x> Background Diet might influence progression of hypertrophic cardiomyopathy (HCM). Objective To investigate whether diet composition could alter clinical, biochemical, or echocardiographic variables in cats with HCM. Animals Twenty‐nine cats with HCM (International Small Animal Cardiac Health Council stage 1b) examined at a university teaching hospital. Methods Randomized, placebo‐controlled trial. After physical examination, echocardiogram, and blood collection, cats were randomized to 1 of 3 diets, which varied in carbohydrate and fat content and ingredients. Measurements were repeated after 6 months. Results There were no significant differences among the 3 groups at baseline. After 6 months, there were no significant changes in the primary endpoints, left ventricular free wall (Group A, P = .760; Group B, P = .475; Group C, P = .066) or interventricular septal thickness in diastole (Group A, P = .528; Group B, P = .221; Group C, P = .097). Group A had significant increases in BUN (P = .008) and cholesterol (P = .021), while Group B had significant increases in BUN (P = .008), cholesterol (P = .007), and triglycerides (P = .005), and significant decreases in NT‐proBNP (P = .013) and hs‐troponin I (P = .043). Group C had significant decreases in body weight (P = .021), left atrial dimension (P = .035), interventricular septal thickness in systole (P = .038), and liver enzymes (P = .034–.038). Conclusions and Clinical Importance These data suggest that diet might influence some clinical, biochemical, and echocardiographic variables in cats with HCM.